Młodzi w Policji - sytuacja kadrowa Policji w latach 2005-2021 = Young people in the Police - staffing situation in the Police force in the years 2005-2021 - Kołodziej, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents an analysis of changes in the staffing situation in the Polish police force in the context of the youngest officers in service, and is a voice in the discussion on the personnel processes in the police force in this respect. The analyses were based on data made available by the Police Headquarters at https://dane.gov.pl/ and focus on information on age groups and length of service of police officers in the years 2005-2021. They also include data on the number of police officers admitted to service and leaving the service during this period (except for 2012 - no data available).
Keywords: policja; rekrutacja do policji; wiek policjantów; staż służby policjantów; police; police recruitment; age of police officers; seniority of service in police force